A phase II clinical trial of Bifidobacterium longum subsp. longum BL21 for preventing acute radiation enteritis among pelvic radiotherapy patients - Yang, Yinyin; Gu, Xuhao; Liu, Chang; Zou, Li; Xie, Liwei; Liu, Yulong; Zhao, Peifeng; Tian, Ye; Cai, Shang (Frontiers in Nutrition, 2025)
BackgroundAcute radiation enteritis (ARE) is a common side effect experienced by patients receiving pelvic radiotherapy (RT). Probiotic supplementation is an emerging strategy for preventing ARE.MethodsThis phase II trial recruited patients with gynecologic or rectal cancers who received pelvic RT with curative or adjuvant intent. During RT, one packet of Bifidobacterium longum subsp. longum BL21 (BL21) powder was self-administered daily. ARE was assessed and classified according to the Radiation Therapy Oncology Group (RTOG) and Common Terminology Criteria for Adverse Events (CTCAE) toxicity grading criteria. We assessed the safety and efficacy of BL21 to prevent ARE and investigate the changes in the intestinal microbiota.ResultsThis study enrolled 52 patients, 8 participants withdrew, and 44 patients being included in the final analysis. The safety profile of BL21 during RT was favorable, and we did not observe any serious adverse events associated with BL21. Compared with our historical control data, these patients exhibited lower levels of ≥ grade 2 ARE and required fewer antidiarrheal medications (n = 12). Most diarrhea cases were classified as grade 1 (n = 22). Analysis of the gut microbiota revealed that the severity of ARE correlates with the abundance of BL21 and the increase in BL21 was associated with greater alpha diversity, an increase in beneficial bacteria, and a decrease in harmful bacteria.ConclusionsThe favorable safety profile, exploratory clinical observations of reduced ARE severity vs. historical controls, and feasible administration support further investigation of Bifidobacterium longum BL21 as a prophylactic candidate for ARE, warranting validation in Phase III randomized controlled trials.Clinical Trial RegistrationChinese Clinical Study Registry (registry ID: ChiCTR2300069881).